2011
DOI: 10.1007/s11604-011-0589-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative follow-up of olecranon fracture by digital tomosynthesis radiography

Abstract: Digital tomosynthesis with flat-panel detector radiography is a novel application that allows easy, swift volume data acquisition of any anatomical site of interest with arbitrary patient posture. A single sweep of the X-ray tube provides multiple tomographic images of high resolution. We present the first patient with olecranon fracture who underwent internal fixation and 1-year postoperative follow-up with tomosynthesis. The minimal metallic artifact by this modality successfully provided detailed informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…For orthopedic applications, DT has been reported to be advantageous for improved imaging of complex anatomic structures, subtle fractures, and the articular surface of joints compared with conventional radiography (11)(12)(13)(14)(15)(16). Specifically, compared with conventional radiography, DT allows easier detection of fractures and can even demonstrate occult fractures not visible at conventional radiography (13) with less tissue overlap, better anatomic visualization, less dependence on the technical skill of the radiographers, and reduced need for painful patient positioning or multiple projections of different views in patients with suspected fractures of fine and complex osseous structures, including carpal bones (eg, scaphoid bone [Fig 8]), metacarpal bones, and tarsal bones (Fig 9).…”
Section: Orthopedic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…For orthopedic applications, DT has been reported to be advantageous for improved imaging of complex anatomic structures, subtle fractures, and the articular surface of joints compared with conventional radiography (11)(12)(13)(14)(15)(16). Specifically, compared with conventional radiography, DT allows easier detection of fractures and can even demonstrate occult fractures not visible at conventional radiography (13) with less tissue overlap, better anatomic visualization, less dependence on the technical skill of the radiographers, and reduced need for painful patient positioning or multiple projections of different views in patients with suspected fractures of fine and complex osseous structures, including carpal bones (eg, scaphoid bone [Fig 8]), metacarpal bones, and tarsal bones (Fig 9).…”
Section: Orthopedic Imagingmentioning
confidence: 99%
“…Manufacturers, such as Hologic and GE Healthcare, offer upgrade paths for standard mammography systems to become breast tomosynthesis capable. Other than DBT, DT is also advantageous in a variety of clinical contexts, including chest, head and neck, orthopedic, and emergency imaging (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The aims of this article are (a) to provide radiologists and radiologic technologists with knowledge about the basic facts and acquisition technique of DT, (b) to illustrate whole-body applications of DT by presenting a broad variety of clinical images, and (c) to demonstrate the clinical utilities and limitations of DT for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…A study of a larger prospective series of wrist fractures [16] showed tomosynthesis to be more useful than radiography but less useful than CT in fracture detection. A few studies have addressed hardware imaging with tomosynthesis, and the results suggest that there may be less artifact than in CT [17][18][19].…”
Section: Digital Tomosynthesis Of Fracturesmentioning
confidence: 99%
“…Some are simple case collections (16,18,19,21); one is a scientific study but with no reported reliability assessment (20). Only three studies have reported reliability of tomosynthesis for assessment of skeletal pathology.…”
Section: Discussionmentioning
confidence: 99%